Papiery wartościowe rynku pieniężnego i ich rola w zarządzaniu płynnością - Galbarczyk, Tamara (Securities on the Money Market and Their Role in Liquidity Managemen, 2007)
The need to maintain financial liquidity and the ability to service indebtedness should be taken into consideration when seeking the right capital structure enabling maximization of profits. Those managing a company's financial liquidity can utilize opportunities provided by securities, especially those in turnover in the money market. Companies announcing their demand for money can issue their own securities in order to acquire capital from other entities. This is an alternative to incurring bank credit, commercial credit or other obligations. However, this entails the need to incur specific costs, and the risk of not selling the securities issued because of the lack of those willing to buy. That is why securities are usually issued by large companies, with an established position, which do not have difficulties selling them. They can issue commercial securities or bonds. Securities issued by other issuers can in turn be kept as a liquidity reserve, especially if they have low investment risk and appropriate liquidity. The advantage of maintaining reserves in this form is that they generate profit unlike the holding of cash. They can be easily converted into cash if the need arises to cover the deficit of liquidity. Companies are especially interested in securities issued by the State Treasury (treasury bonds and exchequer bills), by units of local government (communal bonds), banks (deposit certificates), and by corporations (commercial securities and corporate bonds) in good financial condition.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 175-183